Limits of Government Authority in Business Dealings with Business Entities: A Comparative Study of the Public Contract Regimes of Indonesia and the Netherlands - Muhammad Al-Haadi Nugraha; Ridha Kurniawan; Nova Artika Sari; R.Imam Ghozali; Edi Darmawijaya (JURNAL AKTA, 2026)
Government involvement in business agreements with business entities is expanding along with increasing development needs, but the limits of government authority in public contracts remain undivided. This ambiguity creates normative problems because government contractual actions are often treated as private, even though their substance still carries a public character that must comply with the principles of legality and good governance. The fragmentation of regulations between the Civil Code, the State Administration Law, and the procurement regime increases legal uncertainty, while the Dutch model demonstrates a more stable structure through the integration of administrative principles across all contractual actions. The approach used is a juridical-normative approach, examining laws and regulations, court decisions, legal doctrine, and classical and modern theories of authority. The main objectives of the analysis are to identify the limits of government authority in public contracts, compare the Indonesian and Dutch frameworks, and formulate a more consistent direction for normative reform. The results of the study indicate that Indonesia still positions government contracts as civil agreements, making administrative actions within contracts unamenable to legality testing. The lack of integration between civil and administrative norms opens up room for excessive discretion, creates an imbalance in bargaining power, and increases the risk of ultra vires. In contrast, the Netherlands positions government contracts as public acts, so that every official's actions are subject to the principles of proportionality, prudence, equality, and protection of legitimate expectations, and are subject to judicial review. This integration results in significantly stronger legal certainty and predictability. As a follow-up, a codification of the public contract regime is needed, combining the principles of legality, limits on discretion, objection mechanisms, and public interest parameters within a single, solid normative framework.